PENGARUH MOTIVASI DAN SERTIFIKASI GURU TERHADAP KINERJA GURU - Nurdin, Syahidan (FITRAH: International Islamic Education Journal, 2023)
This study found out influence of work motivation and teacher certificate in SMP Negeri 2 Simpang Tiga Kabupaten Pidie. There are three hypothesis in this research. First, there are influence between work motivation and teachers work. Second, there are influence between teacher certificate and teachers work. Third, there are influence together from work motivation and teacher to teachers work. The instrument that used in this research is Skala Likert construct from many kinds of theory, and it has been formed in variable operational. To know the instrument validity used validity test and reliability test. The implementation in order to motivated all the teachers in SMP Negeri 2 Simpang Tiga Kabupaten Pidie to standard their work motivation and certificate with the result that they can aware to always try their best to get their aim.